COGNITIVE CHARACTERISTICS OF ARGUMENTATION (Web of Teachers: Inderscience Research, 2024)
Cognitive linguistics is a direction in linguistics that is rapidly developing nowadays. It began to take shape at the end of the 20th century, when this field of knowledge moved from the humanities to the cognitive sciences. This field cannot be attributed to a single type of science, as it represents the intersection of several disciplines, such as sociolinguistics, ethnolinguistics and psycholinguistics, which is a characteristic feature of modern humanities research..